Smart Intelligent Safety Management System using ICT - Ki-Young Lee; Min-Soo Kang; Han-Chun Song; Sung-Jai Choi; Jeong-Jin Kang; Rethina Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A traffic accident in a tunnel have occurred continuously all year long for the last five years and the degree of risk for casualties from traffic accidents in a tunnel was higher than that of the casualties from traffic accidents per year. Therefore, the purpose of this study is to design and implement a system that detects the occurrence of abnormality in a vehicle inside a tunnel using a sensor in the tunnel and gives warning to drivers who intend to enter the tunnel from outside in order to prevent the occurrence of an accident inside the tunnel where the degree of risk for casualties is higher. This study also intends to implement a system that uses fire detection sensors in the tunnel to identify the occurrence of a fire inside the tunnel and sends drone to the location where the fire occurred and reports the scene of the fire to 119 in order to prevent the occurrence of a secondary fire inside the tunnel.